LED lights and plant growth regulators enhance the in vitro mass propagation of rosemary ( Rosmarinus officinalis L.) - Davidović Gidas, Jelena; Zeljković, Svjetlana; Đekić, Nikolina; Đurić, Gordana (European journal of horticultural science, 2025)
Rosemary ( Rosmarinus officinalis L.) is a valuable medicinal and aromatic herb produced for its bioactive compounds and commercial applications. However, commonly used methods for rosemary propagation have various limitations that impose the need to create appropriate protocols for in vitro propagation of this species. This research aimed to evaluate the effects of light quality and plant growth regulators (PGRs) on rosemary micropropagation. Explants were cultured on Murashige and Skoog (MS) medium supplemented with varying concentrations of 6-benzylaminopurine (6-BAP), meta-Topolin (mT), 1-naphthaleneacetic acid (NAA), and indole-3-butyric acid (IBA), under different light treatments: fluorescent light (FL) and blue (BL), red (RL), and red-blue (RBL) LED lights. The highest fresh mass was formed by explants grown in medium with mT at 1.0 mg/L + 0.1 mg/L NAA under BL (88.05 ± 2.94 mg), while FL with the same PGR combination resulted in the highest dry mass (12.89 ± 0.55 mg). FL, in combination with 1.0 mg/L mT + 0.1 mg/L NAA, produced the highest number of new shoots (2.07 ± 0.04), and RL, in combination with cytokinin-free MS medium, induced the longest shoots (13.16 ± 0.37 mm). The highest number of nodes (3.91 ± 0.08) was recorded under BL in the cytokinin-free medium. For in vitro rooting, BL combined with 0.1 mg/L mT + 0.5 mg/L IBA produced the highest rooting percentage (80.00 ± 5.77%), the highest number of roots (3.92 ± 0.15), and the longest roots (75.30 ± 1.76 mm). This treatment also resulted in the highest plantlet establishment rate (71.13 ± 4.43%), confirming the synergy between BL and mT + IBA in improving the efficiency of rosemary rooting and acclimatization. These results enable a more straightforward selection of the optimal light spectrum and PGR concentrations for individual stages of the rosemary micropropagation process and highlight the potential of LED lights as a more efficient alternative to traditional fluorescent lamps.